Factors Impacting on Art Major Postgraduate Students’ Satisfaction To Online Learning in Chengdu of China - Yuanbo , Zhong; Pongsatha, Satha (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
The objective of this article was to investigate the critical factors that have a substantial influence on satisfaction about online learning among art major postgraduate students from three universities in the Chengdu region of China. Self-Efficacy (SE), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Service Quality (SQ), Technology (TEC), Perceived Utilitarian Performance (PUP), and Satisfaction (SAT) were all interconnected in the conceptual framework. The researcher utilized the quantitative investigation strategy with 500 samples and distributed the questionnaire to the selected postgraduates at three target colleges. In this survey, a multistage-sampling strategy was used to collect data from the investigation, using judgmental and quota sampling. Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) have been implemented to analyze data. In addition, goodness of model fits, correlation validity, and reliability testing for each component was utilized. Every exogenous variable has demonstrated the which existed the significant impact on the associated endogenous variable, with Perceived Ease of Use (PEOU) providing the greatest consequence on satisfaction. The entire hypotheses have been evidenced to achieve the research purposes. Consequently, for the postgraduate students to acknowledge the effectiveness online instruction, the administrators and instructional staffs who from the graduate school of the public universities should emphasize the latent variables which has exerted the significant effect on satisfaction for the online education and design the interconnected instruction reform according to the findings of this quantitative research.